Burnout, lifestyle and relaxation among dentists in Lithuania: a cross-sectional study - Eglė Slabšinskienė; Andrej Gorelik; Aistė Kavaliauskienė; Apolinaras Zaborskis (BMC, 2021)
Abstract Background The aim of this study was to estimate the association of burnout level with lifestyle and relaxation among dentists in Lithuania. A better understanding of this association could help in the development of targeted interventions to prevent burnout among these professionals. Methods The survey was conducted among practising dentists (N = 380) using the Maslach Burnout Inventory (MBI) and an authors' proposed scale to measure lifestyle and relaxation. Poisson regression was applied to examine the association between variables. Results Regular cigarette smoking among dentists in Lithuania was 16.8 % and alcohol consumption was 31.3 %. Some forms of active relaxation were also common: regular playing sports (57.9 %), and spending time in nature (61.4 %). Emotional exhaustion (EE) and depersonalization (DP) burnout dimensions were negatively related to the regular use of illegal substances, alcohol, medication and smoking, while personal achievement (PA) was negatively related to smoking only. Dentists who regularly exercised had significantly lower EE and DP sum scores, and better assessments of PA. There were also positive relationships of EE, DP and PA sum scores with the variables of relaxation (e.g., spending time with family or friends, visiting a theatre, engaging in art, listening to music). Conclusions It was concluded that the burnout dimensions are negatively associated with unhealthy lifestyle factors and positively associated with active relaxation among dentists in Lithuania. Therefore, burnout prevention should target specific lifestyle and relaxation improvement strategies.